The Intensity of Village-Owned Enterprises in Village Community Welfare - Alwin Teniro; Zainudin Zainudin; Yuli Santri Isma; Hajar Ashwad; Basyirah Basyirah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The problem to be resolved in this study is whether BUMK Subur Makmur as a working capital lender plays a role in moderating the impact of family income on community welfare. The aim is to analyze the role of BUMK in improving the welfare of the local community. Descriptive methods were used in this study, where primary and squander data were collected by direct observation and questionnaires, then the data was processed and presented in the form of tables/graphs, then analyzed with Moderated Regression Analysis (MRA). The results of the study found that the effect of working capital on community welfare without interaction variables is not significant, as well as the influence of interaction variables on community welfare is not significant, meaning that working capital does not moderate the effect of disposable income on community welfare, therefore the role of BUMK Subur Makmur has not been able to strengthen the influence of disposable income on improving the welfare of local communities.